2017
DOI: 10.1088/1755-1315/85/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Pre-slaughter stress and pork quality

Abstract: Abstract. Stress is an inevitable consequence of handling of animals for slaughter. Stress conditions during transport, lairage and at slaughter induce undesirable effects on the end quality of meat such as pale, soft, exudative meat and dark firm dry meat. Hence, it is very important to define appropriate parameters for objective assessment of level of stress. Attempts to define measures of stress have been difficult and no physiological parameter has been successfully used to evaluate stress situations. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
6
0
4
Order By: Relevance
“…На сьогодні відомо [10,7], що якість м'яса безпосередньо залежить від важкості стресу, який відчувала тварина до забою. Зокрема м'язові вуглеводи (глюкоза та глікоген) за дії анаеробного окиснення метаболізуються в лактат, що призводить до зниження pH м'яса.…”
unclassified
See 1 more Smart Citation
“…На сьогодні відомо [10,7], що якість м'яса безпосередньо залежить від важкості стресу, який відчувала тварина до забою. Зокрема м'язові вуглеводи (глюкоза та глікоген) за дії анаеробного окиснення метаболізуються в лактат, що призводить до зниження pH м'яса.…”
unclassified
“…У такому випадку зниження pH м'яса впродовж його дозрівання буде надто швидким. У результаті швидкого затвердіння м'язових волокон пошкоджується їхня структура, відбувається надлишкова втрата вологи та зміна кольору, і як наслідок -зниження якості та терміну придатності м'яса [10,7]. З огляду на це, одним з провідних чинників, які впливають на якість м'яса забійних тварин, є рівень кортизолу в крові, оскільки цей глюкокортикоїдний гормон є пусковим механізмом розвитку ланцюга стресових біохімічних реакцій.…”
unclassified
“…Moreover, it is well known that transport is a stressful process to pigs (Bozzo et al, 2020;Gerritzen et al, 2013;McGlone et al, 2014;, that can compromise animal welfare according to several factors, of which transport distance and duration can be cited MOTA-ROJAS et al, 2006;BRANDT;BOZZO et al, 2020), despite no effects from distance has been reported to the incidence of skin lesions in Belgian (DRIESSEN; VAN BEIRENDONCK; BUYSE, 2020), Canadian (SCHEEREN et al, 2014) and Mexican studies (Becerril-Herrera et al, 2007), contrary to what was observed in this study. Also, it is important to highlight that due to interaction between many factors involved in pre-slaughter operations, such as loading and unloading, microclimatic conditions, journey duration, stocking density, floor type of the vehicle, vibration and fasting (BRANDT; AASLYNG, 2015); it's difficult to stablish transport impact by itself (STAJKOVIĆ et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A maioria das lesões percebidas nos abatedouros são decorrentes de traumas (BOTTACINI et al, 2018). Essas lesões traumáticas são ocasionadas por comportamentos agressivos ou aversivos e influenciadas por diversos fatores, tais como o carregamento e descarregamento, duração do transporte, condições climáticas (umidade e temperatura), localização dos animais nos compartimentos do caminhão , condições das rodovias, tipo do piso do caminhão, privação de água e alimento (DALLA COSTA et al, 2016b), mistura de animais provenientes de diferentes lotes (GOSÁLVEZ et al, 2006;BRANDT;STAJKOVIĆ et al, 2017;BOTTACINI et al, 2018), tamanho e tipo de piso das pocilgas, densidade (RABASTE et al, 2007;ČOBANOVIĆ et al, 2016bČOBANOVIĆ et al, , 2016aSTAJKOVIĆ et al, 2017), descanso pré-abate ČOBANOVIĆ et al, 2016aČOBANOVIĆ et al, , 2016b; DRIESSEN; VAN BEIRENDONCK; BUYSE, 2020a) e condução à insensibilização .…”
Section: Lesões Como Indicadores De Bem-estar Animalunclassified
See 1 more Smart Citation